EŞREF PAŞA DÎVÂNI - DOĞAN, SERAP URGUN (Fırat Üniveristesi, 2010)
Bu çalışmada, 19. Yüzyılda yaşamış Div?n Edebiyatının sona erdiği bir dönemde, eski şiir geleneğini devam ettiren Eşref Paşa'nın Div?nı'nı edebiyat gönüllerinin hizmetine sunmayı hedefledik. Eşref Paşa'nın hayatı, eseri ve Div?nı, devir (19.yüzyıl) ,şahsiyet, eser ekseninde ele alınarak incelenmiştir. Transkripsiyon harfleriyle yeniden yazılmıştır, Div?n'ın tıpkıbasımı kitap arkasında verilmiştir.

In this study, we saw ourdelf obliged to dedicate to put the collected poems of Eşref Pasha, lived in 19 th century and carried on his early custom poems when classical ottoman poetry came to end,into service fort he volunteers of the literature.The life Eşref Pasha, his Works and his collected poems were researched as a part of age (19 th century) personality and work. The collected poems were written using the transcriptional letters and its facsimile was given at the back of the book.
Keywords: Türk Dili ve Edebiyatı